Evaluation of choroidal thickness, retinal nerve fiber layer thickness, macular thickness and retinal vessel diameter by optical coherence tomography in patients with peripheral arterial disease - Ufuk Turan Kürşat Kormaz; Enes Uyar; Fatih Ulaş; Abdulgani Kaymaz; Adem Soydan (Journal of Contemporary Medicine, 2021)
Aim: To evaluate retinal nerve fiber layer thickness, macular thickness and retinal vessel diameter by optical coherence tomography in patients with peripheral artery disease. Materials and Methods: 35 patients with a diagnosis of peripheral arterial disease (PAD) and 32 healthy individuals (control group) were included in the study. Retinal thickness (RT), choroidal thickness (CT) in enhanced depth imaging (EDI) mode, retinal nerve fiber layer (RNFL) thickness, retinal artery and vein diameters were measured with optical coherence tomography (OCT) device. Results: The mean age of the PAH group included in the study was 59.4±11.9 and the mean age of the control group was 55.5±5.3 years. A statistically significant difference was observed between the two groups in the values obtained from the CT in the subfoveal region of the EDI measured from three different regions and the nasal quadrant of the RNFL measured from 7 quadrants (p=0.03 and p=0.03, respectively). On the contrary, no statistically significant difference was observed in EDI and other measurements of RNFL, RT values, artery and vein diameters (p values were between 0.08-1.00). Conclusion: In patients with PAD, it is important to determine the RNFL and CT to be thinner. It can be a guide in more comprehensive studies in the future.